SHARIA MANAGEMENT PERSPECTIVE THROUGH LEADERSHIP AND ASSET MANAGEMENT IN IMPROVING COMPANY PERFORMANCE IN KLAMBIR LIMA VILLAGE, DELI SERDANG REGENCY - Robain, Wilchan; Harianto, Harianto (Proceeding International Seminar of Islamic Studies, 2023)
The research method used in the study entitled ‘Sharia Management Perspective Through Leadership and Asset Management in Improving Company Performance at the Klambir Lima Estate, Deli Serdang Regency’ is a quantitative model using a questionnaire as a data collection tool which is distributed to company employees at the Klambir Lima Estate. Deli Serdang Regency. The data analysis in this study used path analysis assisted by SPSS version 16 for Windows. The results show that the variables of Sharia Management Perspective and Leadership simultaneously had a positive and significant effect on Asset Management in Klambir Lima Gardens, Deli Serdang Regency. Asset management partially and simultaneously has a positive and significant effect on company performance in Klambir Lima Plantation, Deli Serdang Regency.